Reproductive aspects of Chiton virgulatus in Bahía de La Paz, Gulf of California, Mexico - Vélez-Arellano, Nurenskaya; García-Domínguez, Federico Andrés; Holguin-Quiñones, Oscar Efraín; Obeso-Nieblas, Maclovio (Revista de Biología Marina y Oceanografía, 2020)
This study analyzed the reproductive cycle of Chiton virgulatus and its relationship with air temperature (AT) sea and surface temperature (SST), photoperiod, and tidal cycle (TC) in Bahía de La Paz, in the coast of the Gulf of California. Monthly samples were collected from September 2008 to September 2009. The parameters recorded included total length, total weight, and gonad weight of each organism; the gonad was processed using a histological technique, and the gonadal index and length at first maturity (L50) were estimated. C. virgulatus displays partial spawning with a reproductive peak in summer and autumn (July to December). The frequency of ripe organisms was associated with rises in SST (30.6 ºC), AT (29.9 ºC), and TC (68 cm, high tidal), while photoperiod (longer days) regulated the frequency of developing organisms. The length at first maturity was 29.7 mm. Chiton virgulatus is a polyplacophoran species in which high temperatures and high tides influence reproductive timing, while an increase in daylight boosts gonad development.